A New Approach in the Production of Electrical Motors Using Only Machining Processes - Hahn, Ingo; et al. (EDPC 2011, 2011)
As a new possibility of producing the electrical steel sheets of electrical motors, a motor sample was produced using just machining processes such as turning, drilling, milling and sawing. Therefore several strategies in the production flow were considered and tested. The idea behind this method of producing a motor is to avoid the expensive cutting processes and material deterioration. On the one hand punching, as the most common cutting method of electrical steel sheet, is only cheap for useful for high volume and not for samples or small series, on the other hand laser cutting, which is suitable for single production of motors, requires expensive tools. Moreover punching and laser cutting deteriorate the electrical steel sheets close to the cutting edges. Since machining processes can be adjusted in speed and cooled with a fluid, a less distinctive effect can be assumed. © 2011 IEEE.
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.LEEAS.anewap
Keywords: Drilling; electrical steel sheets; machining process; turning

A simple method for the parameter identification of the Jiles-Atherton model using only symmetrical hysteresis loops - Hahn, Ingo; Lindner, Andreas; et al. (IECON 2013, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEEAS.asimpl

Comparison of Soft Magnetic Composite (SMC) and Electrical Steel - Böhm, Andreas; Hahn, Ingo (Proceedings 2012 2nd International Electric Drives and Production Conference, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEEAS.compar

Identification of time-variant high frequency parameters for sensorless control of PMSM using an internal model principle based high frequency current control - Seilmeier, Markus; Böhm, Andreas; Hahn, Ingo; Piepenbreier, Bernhard (2012)
Standstill and low speed self-sensing based field oriented control of PMSM using the high frequency signal injection method requires a sufficient saliency ratio of the high frequency differential inductances of the machine. Therefore these inductances need to be known precisely to be able to guarantee stability of the sensorless control. In order to perform the identification, the conventional field oriented control scheme is extended by additional PI-type controllers in a positive and negative sequence high frequency coordinate system, thus resulting in zero steady state control error in case of superimposed sinusoidal high frequency test current reference values. Moreover the extended control scheme provides a direct demodulation of sine and cosine parts of the high frequency control signals and therefore enables a direct identification of all model parameters relevant for HF injection based sensorless control (differential self-and mutual inductances and high frequency resistances). In contrast to conventional methods, no prerequisites for the parameters or its' dependencies have to be fulfilled.
Keywords: nonlinear coordinate transformation; differential inductances; field-oriented control; internal model principle; parameter identification; PMSM; sensorless control; test current control

Identification of time-variant high frequency parameters for sensorless control of PMSM using an internal model principle based high frequency currrent control - Böhm, Andreas; Seilmeier, Markus; Hahn, Ingo; Piepenbreier, Bernhard (20th International Conference on Electrical Machines, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEEAS.identi

Influence of geometric parameters and cutting edge deterioration on the differential inductances. - Hahn, Ingo; Böhm, Andreas (IEEE International Symposium on Sensorless Control for Electrical Drives (SLED 2014), 2014)
A prerequisite for self-sensing field oriented control of PMSM for standstill operation is a sufficient saliency ratio (magnetic anisotropy) of the differential inductances over the desired operating area. High frequency injection methods are very common in order to perform saliency tracking based self-sensing operation. Vanishing saliency for certain operating points or a change of the sign of the inductance difference, which needs to be known for the self-sensing algorithm, causes loss of stability of the self-sensing control method. This paper uses a simple, parameterized Finite-Element model in order to simulate the influence of geometric parameters and cutting edge deterioration. The simulations have shown that the cutting edge deterioration has only a slight influence on the saliency ratio of the differential inductances, although worst case conditions are assumed for the deterioration. This result is verified on a FE-model of a real PMSM. The most significant influence on the saliency ratio derives from the size of the tooth tip. For low ratios between stator yoke height and tooth width the area with vanishing magnetic anisotropy is increased. The area of magnetic anisotropy is increased with the width of the magnets, however the value of the anisotropy is decreased for large magnet widths. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.influe
Keywords: cutting edge deterioration; differential inductances; geometric parameters; magnetic anisotropy

Influence of Partly Closed Slots on the Differential Inductances - Graus, Johannes; Seilmeier, Markus; Hahn, Ingo; et al. (SLED, 2012)
A prerequisite for sensorless field oriented control of permanent magnet synchronous machines (PMSMs) at very low speed and standstill operation using signal injection methods is a sufficient saliency ratio of the differential inductances throughout the desired operating area. High frequency signal injection methods are very common in order to perform saliency tracking based sensorless operation. Vanishing saliency for certain operating points or a change of the sign of the difference of the differential inductances, which needs to be known for the sensorless algorithm, causes the loss of stability of the sensorless control method. A closed or partly closed stator slot geometry tends to show a local current dependent loss of the saliency even for low currents. This phenomenon typically shows up as a star-shaped pattern of the inductance surface as discussed further within this paper. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEEAS.influe_7
Keywords: Closed slots; differential inductances; permanent synchronous machine; sensorless position detection; standstill operation

Influence of Stator Saturation on the Differential Inductances of PM-Synchronous Machines with Concentrated Winding - Graus, Johannes; Hahn, Ingo; et al. (SLED 2012, 2012)
For sensorless position detection of permanent magnet synchronous machines at very low speed and standstill, signal injection methods are commonly used. As a prerequisite these so called saliency-tracking methods require a differential magnetic anisotropy of the machine, which is both position and load dependent and thus varying during operation. So the performance of sensorless operation strongly depends on the machine design. To investigate the influence of the stator saturation a machine model based on a magnetic equivalent circuit is presented in this document. This model is then used to analyze the differential inductances of a machine with concentrated windings. The results show that for some angles of the current vector the inductances do not vanish even for high currents. This phenomenon is explained by analyzing the flux paths. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEEAS.influe
Keywords: concentrated winding; cross saturation; differential magnetic anisotropy; magnetic equivalent circuit; permanent magnet synchronous machine; sensorless position detection

Influence of Turning on the Magnetic Properties of Electrical Steel in the Production of Electrical Machines - Böhm, Andreas; Hahn, Ingo (International Electric Machines and Drives Conference 2011 (IEMDC 2011), 2011)
This paper presents a method to determine the influence of a turning process on the magnetic properties of non-orientated electrical steel sheets. This is done by measuring the magnetization curve of ring specimens by using them as a kind of transformer core. The magnetization curve can be calculated by measuring the current on the primary side and the voltage on the secondary side which has opened clamps. To determine the influence of the turning process two approaches are considered. The first one compares two turned ring specimens of which one consists of two concentric rings so that the cutting length is doubled. The second approach compares a turned ring specimen with a laser and a water jet cut specimen. The measurements have shown that turning has only a slight influence on the magnetic properties. It is about the same as water jet cutting and less than laser cutting for low field strengths. © 2011 IEEE.
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.LEEAS.influe
Keywords: Electrical steel; laser cutting; magnetic properties; turning; waterjet cutting

Measurement of Magnetic Properties of Steel at High Temperatures - Böhm, Andreas; Hahn, Ingo (IECON 2014, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.measur